Comparasion of composition of brake pad hardness and wearness - Mulia Mulia (Trigin Publisher, 2023)
This study aims to identify the most optimal material composition in achieving the best combination of hardness and wear. The experimental method was conducted using a special test bed designed to test the mechanical properties of various material compositions. The material specimens used were weighed before and after the test to calculate the wear rate by observing the change in specimen mass. The results showed that the 50:50 material composition performed significantly better than the 60:40 composition in terms of hardness and wear properties. These findings suggest that the 50:50 composition may be a superior choice in various applications where a combination of strength and wear resistance is required, such as in the manufacturing industry, materials engineering, or the automotive sector. This research provides valuable insights into material selection that can improve the performance and durability of the final product.